PENDIDIKAN BERBASIS MULTIKULTURAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KERJASAMA - Harun Harun; Nurlaili Nurlaili; Alimni Alimni (Raudhah - Proud To Be Professional, 2023)
This study aims to describe and analyze how the planning, implementation, supporting factors and inhibiting factors and evaluation of multicultural-based education. This type of research is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. The results of this study indicate: 1) Planning in multicultural-based education to create peaceful cooperation "is under each religion, and there is no presumption of unfair treatment of non-Muslim students. So SMK Negeri 3 Seluma, as conveyed by the PAI teacher, states that the school is very supportive of all extra-religious activities for each of their respective religions." 2) educators must be swift and adept in carrying out teaching and learning activities. Especially in schools with many different beliefs, ethnicities, cultures and customs. 3) Supporting Factors The existence of sophisticated IT assistance will make them more interested in learning and honing their abilities, and they must be able to understand the child's character while Inhibiting factors or obstacles encountered in carrying out an activity. There are many "differences in the character of children, whether it is the nature or behaviour of diverse students, idealism between each religion, environmental factors that vary from ethnicity, culture and religion." 4) Implemented tentatively; if problems are found during implementation, they will find solutions and solutions immediately.